2003
DOI: 10.1093/jn/133.5.1452s
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Altered Immune function

Abstract: Zinc is known to be essential for all highly proliferating cells in the human body, especially the immune system. A variety of in vivo and in vitro effects of zinc on immune cells mainly depend on the zinc concentration. All kinds of immune cells show decreased function after zinc depletion. In monocytes, all functions are impaired, whereas in natural killer cells, cytotoxicity is decreased, and in neutrophil granulocytes, phagocytosis is reduced. The normal functions of T cells are impaired, but autoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
398
2
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(419 citation statements)
references
References 62 publications
7
398
2
12
Order By: Relevance
“…20 HIV infection has been reported to be associated with increased proinflammatory cytokines 21 which was reported to lower the plasma levels of zinc but raises the level of Copper. 22 The results of the present study showed that there is significant (p ≤ 0.05) decrease in the mean plasma zinc levels in patients when compared with mean plasma zinc level of control group. This finding agreed with the studies of Khalili et al, 8 Lawal et al 16 and Mohamed et al 23 who reported that there was a significant (p ≤ 0.05) decrease between zinc levels in HIV positive patients when compared with zinc level of the control group.…”
Section: Cd4 Counts and Some Haematological Parameters Of Hiv Positivsupporting
confidence: 44%
“…20 HIV infection has been reported to be associated with increased proinflammatory cytokines 21 which was reported to lower the plasma levels of zinc but raises the level of Copper. 22 The results of the present study showed that there is significant (p ≤ 0.05) decrease in the mean plasma zinc levels in patients when compared with mean plasma zinc level of control group. This finding agreed with the studies of Khalili et al, 8 Lawal et al 16 and Mohamed et al 23 who reported that there was a significant (p ≤ 0.05) decrease between zinc levels in HIV positive patients when compared with zinc level of the control group.…”
Section: Cd4 Counts and Some Haematological Parameters Of Hiv Positivsupporting
confidence: 44%
“…[34][35][36] In contrast, the production of TNF-a and IL-6 can be increased through zinc supplementation in PBMC. 4,7 This study indicates that TNF-a and IL-6 production is decreased after zinc deprivation for three days. In the context of a reprogramming of the immune system during zinc deficiency, 9 a lower release of pro-inflammatory cytokines seems adequate: TNF-a and IL-6, among other cytokines, have many functions connecting the innate with the adaptive immune system.…”
Section: Discussionmentioning
confidence: 77%
“…6 Lipopolysaccharide (LPS), part of the cell wall of gramnegative bacteria, is one of a myriad of agents that leads to secretion of monokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-6. Their release in response to stimulation using LPS can be enhanced in peripheral mononuclear blood cells (PBMC) by zinc supplementation, 4,7 and intracellular zinc signals are required for the production of pro-inflammatory cytokines in response to LPS. 8 Moreover, secretion of proinflammatory cytokines can also be directly induced by incubation with high extracellular Zn 2+ concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 49 and 58% of 51-70 y olds and 70 þ y olds, respectively, are zinc inadequate (Briefel et al, 2000). The effects of zinc deficiency on immune function have been reasonably well documented, with substantial effects reported on CMI (Shankar & Prasad, 1998;Fraker et al, 2000;Rink & Gabriel, 2000;Rink & Gabriel, 2001;Ibs & Rink, 2003). Zinc deficiency also results in depressed innate immunity (Keen & Gershwin, 1990;Prasad, 2000;Dardenne, 2002).…”
Section: Introductionmentioning
confidence: 99%